Pertanggungjawaban Pidana dan Penerapan Keadilan Restoratif terhadap Korporasi sebagai Subjek Tindak Pidana - Silalahi, Lamgok Heriyanto; Sudjiarto, Tatok; Silalahi, Fernando (VISA: Journal of Vision and Ideas, 2025)
This study discusses corporate criminal liability in Indonesia under the Colonial Penal Code and the new National Penal Code. While corporations contribute significantly to economic development, they also engage in criminal activities affecting society. Previously, the Colonial Penal Code did not recognize corporations as criminal subjects, but the National Penal Code, effective in 2026, accommodates corporations as entities subject to prosecution. This research examines theories of corporate criminal liability, including vicarious liability and strict liability. Moreover, it highlights the application of restorative justice, which focuses not only on punishment but also on restoring conditions involving offenders and victims. Through more comprehensive criminal sanctions, the National Penal Code provides space for conflict resolution in a fairer and more recovery-oriented manner, particularly for corporations as criminal subjects. The restorative justice approach also aims to encourage active participation of both victims and offenders in resolving the consequences of corporate crime.